Chitosan Incorporated with Stingless Bee Propolis for Active Food Packaging Application - Nik Azmi, Nik Nur Ashirah; Basri, Hatijah; Atqiya Muslihati (Enhanced Knowledge in Sciences and Technology, 2021)
Food packaging is required in order to protect the food from contamination. The current globalizations on consumers demand towards food safety products have led to the innovation of food packaging technology, in which less synthetic chemical to be used. The use of natural substances such as chitosan has been greatly studied and incorporation of natural antimicrobial agent such as propolis helps to improve the functionality of the food packaging. In this study, chitosan films containing 0, 2.5, 5, and 10 % propolis extract concentration were developed. Changes in the Fourier transform infrared spectra of the films were observed when propolis extract was incorporated, showing some interactions occurred between chitosan and propolis polyphenols. The addition of the propolis has also resulted in reduction in contact angle measurement of the films. The film’s antimicrobial property was determined using agar diffusion technique. Results showed chitosan films containing propolis extract exhibited significant inhibition ring against E. coli and B. cereus.